2012
DOI: 10.1038/clpt.2011.269
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Warfarin Clearance Associated With the CYP2C9 R150H (*8) Polymorphism

Abstract: The cytochrome P450 (CYP) 2C9 R150H (*8) allele occurs commonly in African Americans and is associated with lower warfarin dose requirements. We examined whether the CYP2C9*8 allele impacts warfarin clearance through a pharmacokinetic study in warfarin-treated African American patients and an in vitro kinetic study of S-warfarin 7-hydroxylation using cDNA-expressed CYP2C9 enzymes. We observed a 30% reduction in the unbound oral clearance of S-warfarin and 25% lower R- to S-warfarin plasma concentration in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 32 publications
3
74
0
1
Order By: Relevance
“…Since the formation of an MI complex is dependent upon catalytic rate, the susceptibility to MBI is expected to be dependent upon the relative activities of cytochrome P450 variants (Polasek and Miners, 2007;Orr et al, 2012). To verify that formation of a reactive metabolite(s) of noscapine by CYP2C9 is responsible for the MBI by noscapine, the kinetics of CYP2C9 inhibition were characterized using CYP2C9.2 and CYP2C9.3 variants that are known to exhibit decreased enzyme activity (Liu et al, 2012). Surprisingly, our results showed that the inactivation of CYP2C9 by noscapine was .2-fold more efficient (i.e., k inact /K I ) for CYP2C9.2 and CYP2C9.3 than for CYP2C9.1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the formation of an MI complex is dependent upon catalytic rate, the susceptibility to MBI is expected to be dependent upon the relative activities of cytochrome P450 variants (Polasek and Miners, 2007;Orr et al, 2012). To verify that formation of a reactive metabolite(s) of noscapine by CYP2C9 is responsible for the MBI by noscapine, the kinetics of CYP2C9 inhibition were characterized using CYP2C9.2 and CYP2C9.3 variants that are known to exhibit decreased enzyme activity (Liu et al, 2012). Surprisingly, our results showed that the inactivation of CYP2C9 by noscapine was .2-fold more efficient (i.e., k inact /K I ) for CYP2C9.2 and CYP2C9.3 than for CYP2C9.1.…”
Section: Discussionmentioning
confidence: 99%
“…At different time points (0-30 minutes), an aliquot (10 ml) was transferred into a secondary incubation system containing (S)-warfarin (25 mM), and 7-hydroxywarfarin concentrations were measured by LC-MS/MS. The concentration of warfarin in the secondary incubation system was determined to be .4 times higher than the apparent K m values obtained from different enzyme sources (Hutzler et al, 2009;Liu et al, 2012). The observed rates of inactivation (k obs ) were determined from the slopes of residual CYP2C9 activity versus time plot.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been identified as the most common defective alleles and have exhibited reduced metabolic activities, both in vitro and in vivo, for the CYP2C9 substrates, such as warfarin. In addition to these two common alleles, other allelic variants, such as CYP2C9*4 (Lee et al, 2007), CYP2C9*5 (Dickmann et al, 2001), CYP2C9*8 (Liu et al, 2012), CYP2C9*11 (Tai et al, 2005), CYP2C9*12 (O'Brien et al, 2013), CYP2C9*14 (Lee et al, 2014), CYP2C9*35 (Ciccacci et al, 2011), CYP2C9*57 (Nahar et al, 2013), and CYP2C9*58 (Luo et al, 2014), were reported to affect warfarin sensitivity. In this study, we present the case of a Chinese warfarin-sensitive patient who requires only one-half of the normal oral warfarin dose.…”
Section: Introductionmentioning
confidence: 99%